2016
DOI: 10.1152/ajpregu.00510.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular function, compliance, and connective tissue remodeling in the turtle,Trachemys scripta, following thermal acclimation

Abstract: Low temperature directly alters cardiovascular physiology in freshwater turtles, causing bradycardia, arterial hypotension, and a reduction in systemic blood pressure. At the same time, blood viscosity and systemic resistance increase, as does sensitivity to cardiac preload (e.g., via the Frank-Starling response). However, the long-term effects of these seasonal responses on the cardiovascular system are unclear. We acclimated red-eared slider turtles to a control temperature (25°C) or to chronic cold (5°C). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Prior studies have also reported a net systemic blood flow pattern [i.e. right-left (R-L) shunt] in T. scripta (Wang and Hicks, 1996a;Hicks and Wang, 1998;Crossley et al, 2000;Krosniunas and Hicks, 2003;Galli et al, 2004;Keen et al, 2016). However, we are among the first to assess intracardiac shunting in the snapping turtle (Steggerda and Essex, 1957), and it is unclear whether the direction of shunting is similarly variable in this species.…”
Section: Fasted Measurementsmentioning
confidence: 82%
“…Prior studies have also reported a net systemic blood flow pattern [i.e. right-left (R-L) shunt] in T. scripta (Wang and Hicks, 1996a;Hicks and Wang, 1998;Crossley et al, 2000;Krosniunas and Hicks, 2003;Galli et al, 2004;Keen et al, 2016). However, we are among the first to assess intracardiac shunting in the snapping turtle (Steggerda and Essex, 1957), and it is unclear whether the direction of shunting is similarly variable in this species.…”
Section: Fasted Measurementsmentioning
confidence: 82%
“…Together, these changes preserve whole organism performance across a broader range of temperatures than would otherwise be possible. Similar effects of cold acclimation on the cardiovascular system are observed in turtles (Risher and Claussen, 1987;Keen et al, 2016). Heat acclimation is also a well-established phenomenon in which exposure to elevated temperatures increases the critical thermal maximum of a broad range of organisms (Sinclair et al, 2016;Rohr et al, 2018), including lizards, snakes, and turtles (Murrish and Vance, 1968;Jacobson and Whitford, 1970;Williamson et al, 1989;Brown, 1996).…”
Section: Thermal Acclimation In Juveniles and Adultsmentioning
confidence: 83%
“…Recent work using comparative models, including zebrafish and rainbow trout, have been providing novel insight into how an increase in deposited collagen, permanent in the mammalian heart, may be reversible ( Klaiman et al, 2011 ; Johnson et al, 2014 ). This work has been examining the response of the fish heart, primarily the single cardiac ventricle, to thermal acclimation ( Klaiman et al, 2011 , 2014 ; Johnson et al, 2014 ; Keen et al, 2016a , 2017 , 2018 ; Ding et al, 2021 ). Fish are ectothermic and their physiological temperature is determined by that of their environment.…”
Section: Introductionmentioning
confidence: 99%
“…While there are some fish that significantly reduce physical activity with such a decrease in physiological temperature, salmonids, including rainbow trout, as well as zebrafish do not ( Klaiman et al, 2011 ; Anttila et al, 2014 ; Elliott and Elliott, 2010 ; Rodnick et al, 2004 ; Cortemeglia and Beitinger, 2005 ; Sundin et al, 2019 ). Previous work has demonstrated that the heart of these fish can undergo changes in form, composition and function to help compensate for this change in physiological temperature so as to maintain contractility, and therefore activity of the animal ( Klaiman et al, 2011 , 2014 ; Gamperl and Farrell, 2004 ; Aho and Vornanen, 1999 , 2001 ; Keen et al, 2016b ; Driedzic et al, 1996 ). Cold acclimation of rainbow trout has also been found to cause an increase in the collagen content of the myocardium while warm acclimation reduces collagen content ( Fig.…”
Section: Introductionmentioning
confidence: 99%